Fungsi Sintaktis Kata Jeongmal dalam Bahasa Korea: Analisis Berbasis Korpus - Putri, Anastasia Hannas; Usmi, Usmi (Paradigma: Jurnal Kajian Budaya, 2021)
This paper discusses the syntactic function of the word jeongmal (정말) analyzed through part of speech (품사). In the Korean language, a word can be classified into more than one parts of speech, which is called pumsa tongyong (품사통용) or conversion. An example of pumsa tongyong is the word jeongmal, which can function as an adverb, noun, and interjection. This research shows that such classification makes the word jeongmal has different functions in a syntactic unit, which are main component (predicate), attributive component (adverb), and independent component. In addition, the limitations of the word jeongmal as a noun and POS-tagging error in classifying the word jeongmal as an interjection in the corpus were found. The syntactic function of the word jeongmal is important to be understood because jeongmal is a basic vocabulary with a high frequency of use, both spoken and written. This research is using a quantitative- qualitative method by analyzing a corpus (corpus-based analysis), 21st Century Sejong Corpora (21세기 세종 말뭉치). POS-tagged written and spoken corpus data is used as the data source of this research.